Common theme for drugs effective in overactive bladder treatment: Inhibition of afferent signaling from the bladder - Hood, Brandy (Blackwell Publishing Ltd, 2013)
The overactive bladder syndrome and detrusor overactivity are conditions that can have major effects on quality of life and social functioning. Antimuscarinic drugs are still first-line treatment. These drugs often have good initial response rates, but adverse effects and decreasing efficacy cause long-term compliance problems, and alternatives are needed. The recognition of the functional contribution of the urothelium/suburothelium, the autonomous detrusor muscle activity during bladder filling and the diversity of nerve transmitters involved has sparked interest in both peripheral and central modulation of overactive bladder syndrome/detrusor overactivity pathophysiology. Three drugs recently approved for treatment of overactive bladder syndrome/detrusor overactivity (mirabegron, tadalafil and onabotulinum toxin A), representing different pharmacological mechanisms; that is, β-adrenoceptor agonism, phosphodiesterase type 5 inhibition, and inhibition of nerve release of efferent and afferent transmitters, all seem to have one effect in common: inhibition of the afferent nervous activity generated by the bladder during filling. In the present review, the different mechanisms forming the pharmacological basis for the use of these drugs are discussed.